The Influence of Financial Knowledge, Financial Self-Efficacy, and Financial Stress on Financial Well-Being among University Students Using Paylater in Pontianak City - Dwi Kartika; Edy Suryadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the influence of Financial Knowledge, Financial Self-Efficacy, and Financial Stress on Financial Well-Being among university students using paylater in Pontianak City. This study uses an associative method. The population in this study consists of university students in Pontianak City who use paylater services for transactions, with a sample of 150 respondents determined using purposive sampling techniques. Instrument testing techniques in this study include validity and reliability tests. Furthermore, the classical assumption tests used consist of normality, linearity, and multicollinearity tests. Hypothesis testing was conducted using multiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneous test (F test), and partial test (t test). Based on the results of multiple linear regression analysis, the regression equation obtained is Y = 1.509 + 0.254X₁ + 0.433X₂ − 0.064X3. The correlation coefficient results show a value of 0.769, meaning there is a strong relationship between Financial Knowledge, Financial Self-Efficacy, and Financial Stress on Financial Well-Being. The coefficient of determination shows a value of 0.592, meaning that Financial Well-Being is influenced by Financial Knowledge, Financial Self-Efficacy, and Financial Stress by 59.2%, while the remaining 40.8% is influenced by other variables not examined in this study. The simultaneous test results indicate that Financial Knowledge, Financial Self-Efficacy, and Financial Stress together have a positive and significant influence on Financial Well-Being. Based on the partial test results, it is known that Financial Knowledge and Financial Self-Efficacy have a positive and significant influence on Financial Well-Being. Meanwhile, Financial Stress separately has a negative and significant influence on Financial Well-Being.